Reduction in Gout Attacks Post Sleeve Gastrectomy in Al-Ahsa Hospital, KSA - Hamed Abdullah Alwadaani (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to assess the improvements in patients following sleeve gastrectomy as measured by a subsequent reduction in the incidence of gout attacks. Methods: This retrospective study was conducted at the Bariatric Surgery Department, Al-Moosa Hospital, Al Mubarraz, Saudi Arabia, in 2018. Data for this study were extracted from the records of 3247 patients who had undergone sleeve gastrectomy. The data were analyzed using SPSS version 20. Result: The study included 36 patients who fulfilled the study’s inclusion criteria, with mean age of 39.6 ± 11.6 years, and 26 (72.2%) of them were male. A significant reduction (p = 0.002) in weight was observed in both male and female patients after sleeve gastrectomy; similarly, a significant reduction (p = 0.003) in uric acid levels was also found in both genders. Post-surgery acute gout attack was observed in five (45.5%) cases in the 1 month following surgery and in only one (9.1%) case after 9 months. Various factors were analyzed for their association with postoperative acute gout attack, but only higher baseline body mass index showed a significant association (p = 0.001). Conclusion: The outcome of the study is that sleeve gastronomy significantly reduces gout attacks in obese patients. Along with this conclusion, it was also observed that age, gender, preoperative uric acid levels, and a higher body mass index are risk factors associated with the incidence of gout attacks.